Factors affecting taxpayers to engage in tax evasion on income tax article 25 - Asyifa, Nada; Hendardi, Mohammad Rizky; Simanjuntak, Amanda Elisabech; Anoraga, Bimo Satrio; Wijayanti, Ledia Hanoon; Wijaya, Suparna (WIM Solusi Prima, 2024)
This research aims to identify the factors that influence tax evasion in Indonesia using a literature review approach. The phenomenon of tax evasion has become a serious issue that negatively impacts state revenue and creates injustice among taxpayers. In this study, the researchers examined six relevant journals to identify and categorize the factors influencing tax avoidance behavior by corporate taxpayers and their perceptions of tax evasion. The results indicate that tax rates, the fairness of the tax system, and subjective norms significantly influence tax evasion behavior. The higher the tax rate and the lower the fairness of the tax system and subjective norms, the greater the tendency for taxpayers to engage in tax evasion. Meanwhile, technology and information, discrimination, and understanding of taxation do not have a significant impact on tax evasion. This research emphasizes the need for the formulation of fairer and more effective tax policies to enhance tax compliance. Further research with a more representative sample is needed to strengthen these findings and to delve deeper into the role of technology and information, as well as the understanding of taxation in reducing tax evasion in Indonesia.